Percepción de la contaminación visual y su efecto en la salud de la población en la zona comercial del distrito de Belén, región Loreto, 2020 - Cardenas Yalta, Claudia Katherine (2021)
The study was called "Perception of visual pollution and its effect on the health of the population of the commercial area of the district of Belén, Loreto region, 2020. The objectives of the study were: To determine the perception of visual pollution and its effect on the health of the population in the commercial area of Belén. The onexperimental, quantitative research design was used. The research work is descriptive-transversal. The work was carried out by applying simple random sampling, where 179 people who live in the so-called commercial area of Belén (Calles Próspero, December 9, Arica, Abtao) were chosen. The results achieved were developed through the use of descriptive methods. From the variables analyzed, it turns out that the perception regarding visual pollution in the area is negative, 72.6% answered that they do perceive visual pollution and 50.3% reported having knowledge of the meaning of visual pollution. The first visual contaminant perceived by the population is the mounds of garbage due to the odor that emanates (90%), and outpatient commerce (90%). In second place is between billboards (82%) and wiring (82%). In third place (60%), we have the lack of painting of the houses and 33.5% strongly agree with the lack of plastering on the facades of the houses that causes alteration of the aesthetics of the place. Regarding the effects of visual pollution, it is found that 43.6% present anger, anger and irritability due to the piles of garbage and 40.2% discomfort; 58.6% present discomfort due to outpatient commerce, 58.4% present concern about wiring, and 35.8% and 22.3% present discomfort due to the lack of painting and plastering in the dwellings.